ANALYSIS OF THE OPERATIONAL PATTERN OF THE BILI-BILI RESERVOIR IN GOWA DISTRICT, SOUTH SULAWESI PROVINCE - Rahel E.T. Hendy; Alvin Yesaya; Silvia Gabrina Tonyes; Mawiti Infantri Yekti (Universitas Udayana, 2024)
The Bili-Bili Reservoir serves multiple purposes, including flood control, raw water supply, irrigation, and hydropower generation. In 2021, significant discrepancies were observed between the Annual Reservoir Operation Plan (AROP) and the actual Reservoir Operation Pattern (ROP). during the first 15 days of December 2021, the AROP targeted a rest water level (RWL) of +77.34 m with a planned discharge of 20.27 m³/sec. In contrast, the realized RWL reached +92.35 m with an actual discharge of 45 m³/sec. This study aims to analyze the causes of these differences and compare the reservoir operations outlined in the AROP with those reflected in actual utilization, using an operational pattern simulation based on variations in irrigation water requirement (IWR). Analysis using a dependable flow of 80% shows that the total IWR in the AROP is only 69% of the IWR calculated from actual reservoir utilization, likely due to declining inflow trends and an operational pattern that adjusts to inflow magnitude and rainfall. Meanwhile, the realized IWR is 32% greater than the utilization analysis and 91% greater than the AROP, indicating that the reservoir released more water than planned, following actual inflow conditions. This study highlights the need for more adaptive reservoir operation planning to ensure effective water resource management.